Werkstoffanalytische Betrachtung der Eigenschaften von mittels neuartiger RTM-Fertigungsprozesse hergestellten glasfaserverstärkten Polymerverbunden - Haspel, Benedikt (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2014)
In this work fiber reinforced polymers were characterized. The composites were manufactured with optimized resin transfer molding (RTM) production strategies to make the standard RTM process more efficient. To determine where the potential of the new production techniques is the quasi static mechanical properties were measured and also calculated with an analytical modulation. On this database the different processes were compared to each other.